Diagenetic controls on the isotopic composition of carbonate‐associated sulphate in the Permian Capitan Reef Complex, West Texas. Issue 7 (1st July 2019) - Present, Theodore M.; Gutierrez, Melissa; Paris, Guillaume; Kerans, Charles; Grotzinger, John P.; Adkins, Jess F.
Abstract: Late Palaeozoic‐age strata from the Capitan Reef in west Texas show facies‐dependent heterogeneity in the sulphur isotopic composition of carbonate‐associated sulphate, which is trace sulphate incorporated into carbonate minerals that is often used to reconstruct the sulphur isotopic composition of ancient seawater. However, diagenetic pore fluid processes may influence the sulphur isotopic composition of carbonate‐associated sulphate. These processes variously modify the sulphur isotopic composition of incorporated sulphate from syndepositional seawater in shelf crest, outer shelf, shelf margin and slope depositional settings. This study used a new multicollector inductively‐coupled plasma mass spectrometry technique to determine the sulphur isotopic composition of samples of individual depositional and diagenetic textures. Carbonate rocks representing peritidal facies in the Yates and Tansill formations preserve the sulphur isotopic composition of Guadalupian seawater sulphate despite alteration of the carbon and oxygen isotopic compositions by meteoric and dolomitizing diagenetic processes. However, sulphur isotopic data indicate that limestones deposited in reef and slope facies in the Capitan and Bell Canyon formations largely incorporate sulphate from anoxic marine‐phreatic pore fluids isotopically modified from seawater by microbial sulphate reduction, despite generally preserving the carbon and oxygen isotopic compositions of Permian seawater. Some early and all late meteoric calcite cements have carbonate‐associated sulphate with a sulphur isotopic composition distinct from that of Permian seawater. Detailed petrographic and sedimentary context for carbonate‐associated sulphate analyses will allow for improved reconstructions of ancient seawater composition and diagenetic conditions in ancient carbonate platforms. The results of this study indicate that carbonate rocks that diagenetically stabilize in high‐energy environments without pore fluid sulphate gradients can provide a robust archive of ancient seawater's sulphur isotopic composition.